Assessing Roles of Aggregate Structure on Hydraulic Properties of Saline/Sodic Soils in Coastal Reclaimed Areas - Yuanhang Fei; Dongli She; Shengqiang Tang; Hongde Wang; Xiaoqin Sun; Xiao Han; Dongdong Liu (Agronomy)
During coastal reclamation processes, land use conversion from natural coastal saline/sodic soils to agricultural land changes the soil’s physicochemical properties. However, the impact of soil structure evolution on soil hydraulic properties (SHPs, e.g., hydraulic conductivity and soil water retention curves) during long-term reclamation has rarely been reported. In this study, we aimed to evaluate the effect of reclamation duration and land use types on the soil aggregate stability and SHPs of coastal saline/sodic soils and incorporate the aggregate structures into the SHPs. In this study, a total of 90 soil samples from various reclaimed years (2007, 1960, and 1940) and land use patterns (cropland, grassland, forestland, and wasteland) were taken to analyze the quantitative effects of soil saline/sodic characteristics and the aggregate structure on SHPs through pedotransfer functions (PTFs). We found that soil macroaggregate contents in the old reclaimed areas (reclaimed in 1940 and 1960) were significantly larger than those in the new reclamation area (reclaimed in 2007). The soil saturated hydraulic conductivity (Ks) of forestland was larger than that of grassland in each reclamation year. Soil structure contributed to 22.13%, 24.52%, and 23.93% of the total variation in Ks and soil water retention parameters (α and n). The PTFs established in our study were as follows: log(Ks) = 0.524 − 0.177 × <semantics>Yk3</semantics> − 0.093 × <semantics>Yk1</semantics> + 0.135 × <semantics>Yk4</semantics> − 0.054 × <semantics>Yk2</semantics>, 1/α = 477.244 − 91.732 × <semantics>Yα2</semantics> − 81.283 × <semantics>Yα4</semantics> + 38.106 × <semantics>Yα3</semantics>, and n = 1.679 − 0.086 × <semantics>Yn2</semantics> + 0.045 × <semantics>Yn1</semantics> − 0.042 × <semantics>Yn3<mtext> </mtext>(Y<mtext> </mtext>are<mtext> </mtext>principal<mtext> </mtext>components)</semantics>. The mean relative errors of the prediction models for log(Ks), 1/α, and n were 79.30%, 36.1%, and 9.89%, respectively. Our findings quantify the vital roles of the aggregate structure on the SHPs of coastal saline/sodic soils, which will help us understand related hydrological processes.